Bimbingan Terpadu: Pengabdian Kepada Siswa Tunarungu - Prilia Linda Astuti; Salma Hakiim; Ibrahim Ibrahim (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
In early 2022 the COVID-19 pandemic began to improve after the promotion of vaccination followed by a decrease in the number of Covid-19 cases. Several aspects of life, such as economics, politics, and education, have begun to be reorganized to face the new normal era. This change does not only have an impact on traders, farmers, or teachers. Students also feel the changes, including students with special needs. The service is carried out to deaf students who attend non-inclusive public high schools. Service activities are carried out in several stages, namely: 1) observation and interviews; 2) preparation of lesson plans (RPP); 3) implementation of learning. The learning activities went smoothly even though there were some obstacles that could be overcome immediately. Students can understand and follow learning activities well.